Peripartum dilated cardiomyopathy - Đorđević Spomenka (Sanamed, 2011)
Peripartum cardiomyopathy (PPCM) is a form of dilated cardiomyopathy that is defined as deterioration in cardiac function presenting towards the end of pregnancy or in the months following delivery, where no other cause of HF is found. As with other forms of dilated cardiomyopathy, PPCM involves systolic dysfunction of the heart with a decrease of the left ventricular ejection fraction (EF) with associated congestive heart failure and an i ncreased risk of atrial and ventricular arrhythmias, thromboembolism, and even sudden car¬diac death. m this case report, we describe the development of PPCM in 37 year-old primigravida with a twin pregnancy. It is well-known from literature that twin pregnancy is considered a risk factor for development of PPCM. However, the association of twin pregnancy and PPCM is unclear. Our patient improved remarkably. We review the diagnostic procedures of PPCM and its management. Conclusion: Early diagnosis and intensive treatment by a multidisciplinary team is a prerequisite for improved outcome.